Republic of Azerbaijan : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of Azerbaijan. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with the Republic of Azerbaijan highlights that the economy is continuing to recover from a banking crisis and recession. Looking ahead, economic growth is expected to reach 2.7 percent in 2019 on strong hydrocarbon production and robust domestic demand, benefitting from new spending measures. Gradual and growth-friendly fiscal consolidation is needed to strengthen intergenerational and precautionary buffers while mitigating the adverse impact on the economy. Consolidation could rely on prioritizing and improving the efficiency of spending, rationalizing tax policy, and improving revenue administration. Reducing administrative burden for businesses, encouraging competition, and strengthening governance and transparency would reduce the cost of doing business, foster entrepreneurship, and attract foreign capital. Prioritizing investment for healthcare and education, improving its efficiency, and better targeting of social protection would help nurture human capital and improve productivity. Addressing governance weaknesses is essential to reduce vulnerabilities to corruption. More integrated policies, along with better data availability, would support decision making and credibility, and attract investment.